2014
DOI: 10.1016/j.jpsychores.2014.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Severe depressive symptoms are associated with elevated endothelin-1 in younger patients with acute coronary syndrome

Abstract: Objective To explore the relationship of depressive symptom severity to circulating Endothelin (ET) – 1 in younger patients with acute coronary syndrome (ACS). Younger patients report greater depressive symptom severity, which predicts poorer post-ACS prognosis. The pathways linking depression to post-ACS prognosis require further elucidation. ET-1 is a potent endogenous vasoconstrictor which has been previously linked to adverse post-ACS outcomes. Methods The sample (n=153) included males ≤50 years of age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In our previous cross-sectional study of the current sample, depression symptom severity, as determined by the BDI-II score, was associated with circulating ET-1 levels at the time of hospitalization for an ACS event [13]. Hypothesizing that pathological vascular processes may comprise one of the mechanisms by which depression contributes to adverse post-ACS outcomes, in this prospective study we examined the effects of depression and ET-1 on subsequent events.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our previous cross-sectional study of the current sample, depression symptom severity, as determined by the BDI-II score, was associated with circulating ET-1 levels at the time of hospitalization for an ACS event [13]. Hypothesizing that pathological vascular processes may comprise one of the mechanisms by which depression contributes to adverse post-ACS outcomes, in this prospective study we examined the effects of depression and ET-1 on subsequent events.…”
Section: Discussionmentioning
confidence: 95%
“…The role of ET-1 following ACS events can be detrimental, and in several studies, circulating ET-1 measured soon after ACS was found to strongly predict adverse post- event prognosis [911]. Burg et al demonstrated an association between depression and circulating ET-1 in older patients with chronic stable coronary artery disease (CAD) [12], and in a cohort of younger ACS patients (males ≤50 years of age and females ≤55 years of age), we have previously shown that depression symptom severity was associated with circulating ET-1 at the time of hospitalization [13]. In the current analyses we report on the 2-year follow-up of this cohort and the contribution of depression and ET-1 at the time of index ACS to subsequent major adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the findings of our study, the serum ET-1 content significantly increased, while the NO content decreased notably in rats treated with miR-224 inhibitor in comparison to MI rats without other treatment, which were reversed in rats treated with the inhibitor of the TGF-β/Smad pathway (SB431542). ET-1, a candidate endogenous vasoconstrictor, is found to be associated with adverse outcomes and poor prognosis of ACS (Yammine, Frazier, Padhye, Burg, & Meininger, 2014). NO regulates the coronary blood flow through the process of vasodilatation, preventing the development of coronary circulatory failure and atherosclerosis (Toda, Tanabe, & Nakanishi, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that, in patients with coronary artery disease, the severity of depressive symptoms predicts elevated ET-1 [ 2 , 3 ], therefore, the purpose of the present re-analysis of DIAST-CHF data was to elucidate whether the circulating precursor CT-proET-1 is linked to anxiety, independent of depression. In particular, we aimed to clarify a putative anxiolytic effect due to ET-1, or its precursor molecules or proteolytic fragments, in humans and to decipher its mechanistic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the 21-amino acid neuropeptide ET-1 is also linked to anxiety states has not been investigated so far. However, two studies have reported a positive association between circulating ET-1 levels and depressive symptom severity in patients with coronary artery disease [ 2 , 3 ], indicating that this vasoactive peptide modulates brain functions [ 4 ]. In addition, it was shown that ET-1 decreases the high-affinity uptake of the excitatory amino acid glutamate in primary cultured astrocytes from rat cerebral cortex, suggesting a direct effect on membrane depolarisation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%